Modified translationally controlled tumor protein-derived protein transduction domain enhances nasal delivery of exendin-4 as shown with insulin - Hae-Duck Bae; Moonhee Kim; Joohyun Lee; Kyunglim Lee (Taylor & Francis Group, 2018)
Protein transduction domains (PTDs) have been shown to promote the delivery of therapeutic proteins or peptides into the living cells. In a previous study, we showed that the double mutant of TCTP-PTD 13, TCTP-PTD 13M2, was more effective in the delivery of insulin than the wild-type TCTP-PTD 13. In this study, we applied this approach to the nasal delivery of a different peptide, exendin-4, using as carriers, several modified TCTP-PTDs, such as TCTP-PTD 13M1, 13M2, and 13M3. Nasal co-administration of TCTP-PTD 13M2 with exendin-4 showed the highest exendin-4 uptake among the three analogs in normal rats, and also decreased blood glucose levels by 43.3% compared with that of exendin-4 alone and by 18.6% compared with that of exendin-4 plus TCTP-PTD 13 in diabetic mice. We also designed an additional covalently linked conjugate of TCTP-PTD 13M2 and exendin-4 and evaluated its hypoglycemic effect after subcutaneous or intranasal delivery. Subcutaneous administration of exendin-4 that its C-terminus is covalently linked to TCTP-PTD 13M2 showed hypoglycemic effect of 42.2% compared to that in untreated group, whereas intranasal delivery was not successful in diabetic mice. We conclude that a simple mixing TCTP-PTD 13M2 with peptide/protein drugs can be potentially a generally applicable approach for intranasal delivery into animals.